IDENTIFIKASI KANDUNGAN MINYAK ALPUKAT SEBAGAI BAHAN BAKU INDUSTRI KOSMETIK - Hendra Saputra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
This research has been done regarding to the identification avocado oil (Persea americana.Mill) composition as raw material of cosmetic industry. The usage of the avocado in the West Sumatera is still limited, meanwhile, it has two functions which never known by people. It concerns about the amount of the flesh of avocado and the useness for staple and cosmetics. In this research, the researcher will choose high-yielding variety and local variety in Solok, West Sumatera. This is caused by Solok has a good potential which has a plenty of avocados per year which shown by the statistics Plants of food and Holticulture from West Sumatera at 2012 that Solok has a sharp amount of the production Avocado around 27.281 ton per year. In this research, the oil that is gotten by the process of extraction at the solvent uses a dark-green soxhlet. Then it will be achieved some amount of avocado oils from high -yielding variety at 5,31% and 16,11% on local variety from a wet-basis. On the other hand, it will be then achieved the characteristics of physic-chemistry from the extraction. The composition of fatty acid in the arrangement of Trigliserida can be found by making an early derivation by processing of Methyl Ester. This research shows that a high yielding veriety consists of caprilate acid (1,68%), caprate acid (1,93%), laurate acid (8,62%), miristate acid (3,92%), palmitate acid (20,53%), palmitoleate acid (1,08%), stearate acid (5,61%), oleate acid (26,34%), linolenate acid (4,59%). Baside that, for the local variety consists of caprilate acid (0,92%), laurate acid(9,41%), miristate acid (4,00%), palmitate acid (14,44%), palmitoleate acid (0,84%), oleate acid (14,81%), linolenate acid (1,36%), with the total of Trigliserida component from the avocado oil at 73,85% and 45,78% for a local avocado oil. At the result, the highest percentage of fatty acid is oleate acid, basides, the composition of laurate and palmitate acid is big enough while both fatty acid of high-yielding and local variety come to a laurin-palmito-olein.